Unión Andina de Cementos S.A.A. (UNACEM): Capital Structure Case - Lizarzaburu, Edmundo R. (2015)
This present research paper, introduces one of the most important companies in the local market (Peru), Union Andina de Cementos S.A.A. (UNACEM). The company is engaged in the development and manufacture of clinker, cement and other building materials in the country and abroad, including marketing and sales as well as the operation of the dock facilities and complementary Conchan oil refinery. In the last years, their capital structure and their WACC changed because of the merger between Cementos Andino and Cementos Lima. Also, we considered the macroeconomic environment and the national cement industry, in 2012; the company had a market share of 54% and was the leader of the local market. Additionally, according to the forecast of the national economic institutions, the local construction market will have an increase of 14% in the next years. This research paper is ideal for the analysis of the capital structure of the company with the market value, and could be used within the current context of the construction sector, in view of the new projects and the growth of the local market.